The Ticket to Heaven: A Spiritual Resource for Coping with Disability - Osman Hatun; Fazilet Yavuz-Birben; Zeynep İnce; Gülay Kalkan-Yeni (Spiritual Psychology and Counseling)
This study was conducted to investigate how parents of disabled people deal with the phenomenon of disability, their hardships in accepting the process, and support mechanisms used to deal with the situation. The phenomenological research design was used and 17 in-depth interviews were conducted with parents. Of the interviewed parents’ children, five of them have mental retardation, five have a physical disability, five have both a mental and physical disability, and two have autism spectrum disorder. The obtained data were phenomenologically analyzed with the support of MAXQDA 11. Data were examined in three general categories: difficulty of the process, coping resources, and spiritual coping. Of these categories, difficulty of the process and coping resources are thought to allow for better understanding of spiritual coping, the focus of the study. The sub-themes of shock/collapse, not attributing, fear of losing the child, disappointment, self-blame, loneliness, lack of paternal support, negative environmental effects, concern for the future, and despair is evaluated under the theme of difficulty of the process. The sub-themes of expert support, family support, environmental care, rationalizing, hope, following daily routines, blaming, and unable to be apart from the child is evaluated under the theme of coping resources. The core category of the research, spiritual coping resources, is examined under the categories of acceptance (accepting what comes from God and destiny), giving spiritual meaning (being tested, repentance, fear of God, and being an entrustment from God), and trust in God (resignation, gratitude, and prayer). Recommendations have been presented based on the results of the research.